MOODLE-BASED LEARNING MEDIA DEVELOPMENT OF FLEX MODEL IN IMPROVING MATHEMATICAL HARD SKILLS OF HIGH SCHOOL STUDENTS - Rani Darmayanti; Baiduri Baiduri; Siti Inganah (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The development of the flex media model looks like the beginning of the problems in the classroom, especially in the new normal. Students experience difficulties when given math problems. Students are less able to solve these problems, especially in understanding justifying mathematical ideas and arithmetic skills, and are less interested and enthusiastic when learning. This study aimed to develop a Moodle-based flex model learning media to improve students' mathematical hard skills with three-dimensional material. The study was used to research and develop the four-D model. The instruments used included validation, questionnaires, pre, and post-test questions, small-scale trials of 10 students, and large-scale trials with a purposive sampling technique of 30 class XII students. Data collection techniques include (1) validation questionnaires of media and material experts, (2) practicality questionnaires (student responses), and (3) pre-posttest questions. Material and media expert validator test with very decent results. The results of the student response questionnaire were reasonably practical regarding statements related to the practicality of the Moodle-based flex model media. The N-gain average score indicated a